Going to the Morgue with Andres Serrano: Provocation as Revelation - Sosler, Alex (Religions, 2022)
Originally displayed in Paula Cooper Gallery in New York City’s SoHo district, Andres Serrano’s The Morgue series continued the artist’s controversial and transgressive work. Set against a black backdrop in a mortuary, he photographed dead bodies in different stages of decomposition. In this article, I borrow from Charles Taylor’s cultural analysis of the secular and Flannery O’Connor’s literary theory of the revelatory power of the grotesque to discuss Serrano’s artistic choices. In essence, I argue that his work is not a desecration of humanity but a stark reminder of the sacralization of humanity. As such, Serrano’s work is not provocative for provocation’s sake, but a provocation to poke holes in a disenchanted age. Underneath Serrano’s images is the question: if this is a heap of flesh, why are you provoked? In a culture that avoids death at all costs, Serrano reminds the contemporary world of their mortality with an updated form of memento mori art.